14-3-3z constrains insulin secretion by regulating mitochondrial function in pancreatic b-cells - Mugabo, Y; Zhao, C; Tan, JJ; Ghosh, A; Campbell, SA; Fadzeyeva, E; Paré, F; Pan, SS; Galipeau, M; Ast, J; Broichhagen, J; Hodson, DJ; et al. (American Society for Clinical Investigation, 2022)
While critical for neurotransmitter synthesis, 14-3-3 proteins are often assumed to have redundant functions due to their ubiquitous expression, but despite this assumption, various 14-3-3 isoforms have been implicated in regulating metabolism. We previously reported contributions of 14-3-3z in b-cell function, but these studies were performed in tumor-derived MIN6 cells and systemic knockout mice. To further characterize the regulatory roles of 14-3-3-z in b-cell function, we generated b-cell-specific 14-3-3z knockout mice. Although no effects on b-cell mass were detected, potentiated glucose-stimulated insulin secretion (GSIS), mitochondrial function, and ATP synthesis were observed. 14-3-3z deletion also altered the b-cell transcriptome, as genes associated with mitochondrial respiration and oxidative phosphorylation were upregulated. Acute 14-3-3 protein inhibition in mouse and human islets recapitulated the enhancements in GSIS and mitochondrial function, suggesting that 14-3-3z is the critical isoform in bcells. In dysfunctional db/db islets and human islets from type 2 diabetic donors, expression of Ywhaz/YWHAZ, the gene encoding 14-3-3z, was inversely associated with insulin secretion, and pan-14- 3-3 protein inhibition led to enhanced GSIS and mitochondrial function. Taken together, this study demonstrates important regulatory functions of 14-3-3z in the regulation of b-cell function and provides a deeper understanding of how insulin secretion is controlled in b-cells.